Testosterone Deficiency Caused by Castration Modulates Mitochondrial Biogenesis Through the AR/PGC1α/TFAM Pathway - Liu, Can; Ma, Jideng; Zhang, Jinwei; Zhao, Han; Zhu, Yan; Qi, Jing; Liu, Lingyan; Zhu, Li; Jiang, Yanzhi; Tang, Guoqing; Li, Xuewei; Li, Mingzhou (Frontiers in Genetics, 2019)
Mammalian mitochondrial biogenesis is a complex process involving mitochondrial proliferation and differentiation. Mitochondrial DNA transcription factor A (TFAM), which encodes a major component of a protein-mitochondrial DNA (mtDNA) complex, is regulated by peroxisome proliferator-activated receptor γ coactivator 1α (PGC1α). Testosterone is the primary male sex hormone and plays an increasingly important role in mammalian development through its interaction with androgen receptor (AR). However, the function of AR in mitochondrial biogenesis induced by testosterone deficiency has not been investigated. Here we explored the molecular mechanism underlying the effect of testosterone deficiency on mitochondrial biogenesis using a Yorkshire boar model. Testosterone deficiency caused by castration induced changes in mtDNA copy numbers in various tissues, and AR showed the opposite tendency to that of mtDNA copy number, particularly in adipose tissues and muscle tissues. In addition, castration weakened the correlation of PGC1α and mtDNA copy number, while AR and TFAM showed a relatively high correlation in both control and castrated pigs. Furthermore, luciferase assays revealed that AR binds to potential AR elements in the TFAM promoter to promote TFAM expression. Taken together, testosterone may be involved in the pathway linking PGC1α to mitochondrial biogenesis through the interaction between AR and TFAM.